Consumption of eggs alone or enriched with annatto (bixa orellana l.) does not increase cardiovascular risk in healthy adults. A randomized clinical trial, the eggant study (2023)
ABSTRACT: Most atherosclerotic cardiovascular diseases can be prevented by modifying lifestyles, including unhealthy diets. Eggs contain important carotenoids that may impact cardiovascular risk. The lipid nature of eggs can improve the bioavailability of other carotenoids, such as Annatto (Bixa orellana L.), with reported antioxidant properties. Although numerous studies have shown that there is no association between egg consumption and cardiovascular risk, there is still controversy. In addition, there is limited information about Annatto’s effects on human health. This study evaluated the association between egg consumption and its enrichment with Annatto in lipid biomarkers of cardiovascular disease. In a parallel clinical trial, one hundred and five (n = 105) men and women were randomized by age, sex, and body mass index (BMI), and distributed into three groups. Subjects consumed daily, for 8 weeks, either two eggs, two eggs with Annatto, or two egg whites. Plasma lipids were measured by enzymatic colorimetric methods, plasma apolipoproteins and lipoprotein subfractions and size by nuclear magnetic resonance. There were no differences between groups in age, sex, and BMI. No significant changes were found over time or between groups in plasma triglycerides, LDL cholesterol, HDL cholesterol, apolipoprotein (apo) A1, apo B, or lipoprotein subfraction concentrations. In healthy adults, the intake of two eggs a day, or two eggs with Annatto for eight weeks, did not generate adverse changes in cardiovascular risk markers.